Economic Distress and Labor Market Participation. (28th August 2018) - Stephens, Heather M.; Deskins, John
Abstract: Many of the most deeply and persistently distressed regions of the United States, such as parts of West Virginia, suffer from extremely low levels of labor force participation. These are regions where economic despair seems to have taken hold for generations and which face numerous other impediments to economic prosperity, such as opioid abuse. Better understanding these linkages can lead to policy solutions to help the most disadvantaged places break the cycle of economic despair. Using county‐level data, we begin by estimating a series of models that allow us to understand the drivers of local labor force participation. We also consider how these drivers may differ between rural and urban areas. We then analyze how levels of participation in the labor force are related to other measures of economic distress. We find that there is significant variation in the drivers of rural and urban labor force participation; however, much of the variation can be explained by known factors. Yet, our results also suggest that there remains some portion of the lower levels of labor force participation in West Virginia and Appalachia that cannot be explained by other factors. Since it appears that labor force participation is important to explaining higher levels of employment growth in rural areas, for persistently distressed regions, finding ways to increase labor force participation may be a critical step toward increasing economic prosperity.